Don’t Forget the User: It’s Time to Rethink Network Measurements - Bothra, Rahul; Taneja, Aryan; Bhattacherjee, Debopam; Gandhi, Rohan; Padmanabhan, Venkat; Bhagwan, Ranjita; Natarajan, Nagarajan; Guha, Saikat; Cutler, Ross (ACM HotNets, 2023)
Network measurement has long focused on the bits and bytes — low-level network metrics such as latency and throughput, which have the advantage of being objective and directly characterizing the performance of the network. We argue that users provide a rich and largely untapped source of implicit as well as explicit signals that could complement and expand the coverage of traditional methods. Implicit feedback leverages user actions to indirectly infer the network performance and the resulting quality of user experience. Explicit feedback leverages user input, typically provided offline, to expand the reach of network measurement, especially for newer ones. We analyse two scenarios – capturing implicit feedback through user actions from a large-scale conferencing service, and gathering explicit feedback via social media posts pertaining to the SpaceX Starlink Low Earth Orbit (LEO) satellite network undergoing deployment. We believe our techniques complement the traditional measurement methods and opens a broad set of research directions, ranging from rethinking measurements tools, to designing user-centric networked systems and applications.